Из «истории животных»: собаки при дворе правителей Великого княжества Литовского (до середины XVII в.) - Рагаускене, Р. (Соціум. Альманах соціальної історії, 2013)
Опираясь на концепт «истории животных», в статье делается попытка выяснить отношения великих князей Литвы (до середины XVII в.) со вторым по
популярности после коня питомцем – собакой. Археологический материал и
письменные источники (с конца X в.) показывают, что собаки на территории
современной Литвы жили рядом с человеком в период мезолита и также в ранних обществах балтов. Спираючись на концепт «історії тварин», у статті робиться спроба з’ясувати
відношення великих князів Литви (до середини XVII ст.) з другим за популярністю після коня домашнім улюбленцем – собакою. Археологічний матеріал і
писемні джерела (з кінця X ст.) засвідчують, що собаки на території сучасної
Литви жили поруч з людиною в період мезолиту і також у ранніх суспільствах балтів. This article is based on the concept of ‚the animal history‘. The author tries to
clarify the relationship between the grand dukes of the GDL (until the XVII c.) and
their beloved pets – their dogs, which were in the second place after horses. The
archaeological and written material (from as far back as in the late 10th century)
shows the life of dog sat man's side beginning in Mesolithic Lithuania and including
the early Baltic societies. In the mid-13th-14th centuries, the first Lithuanian rulers
likely kept hunting and guard dogs, but there is a lack of specific data until the late 14th century.